2021
DOI: 10.3390/jcm10112471
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Immunogenicity and Genotoxicity Considerations of Adeno-Associated Virus Vector Gene Therapy for Hemophilia

Abstract: Adeno-associated viral (AAV) vector gene therapy has shown promise as a possible cure for hemophilia. However, immune responses directed against AAV vectors remain a hurdle to the broader use of this gene transfer platform. Both innate and adaptive immune responses can affect the safety and efficacy of AAV vector–mediated gene transfer in humans. These immune responses may be triggered by the viral capsid, the vector’s nucleic acid payload, or other vector contaminants or excipients, or by the transgene produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 144 publications
(307 reference statements)
0
53
0
Order By: Relevance
“…This notwithstanding, in AAV-vector-mediated GRT, expression of a non-self-protein could trigger widespread immune response against the human transgene [ 26 , 27 ], which presents a fundamental challenge to gene therapy [ 22 ]. However, it was observed that AAV-based GRT in neonates, in the critical period of immunological development, could induce an immunological tolerance to the transgene product, improving the safety and tolerance of gene therapy [ 22 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This notwithstanding, in AAV-vector-mediated GRT, expression of a non-self-protein could trigger widespread immune response against the human transgene [ 26 , 27 ], which presents a fundamental challenge to gene therapy [ 22 ]. However, it was observed that AAV-based GRT in neonates, in the critical period of immunological development, could induce an immunological tolerance to the transgene product, improving the safety and tolerance of gene therapy [ 22 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…An adeno-associated viral vector system is currently employed in a Phase II study on the treatment of Huntington's disease to permit the cellular delivery of the amiRNA drug AMT-130 (ClinicalTrials.gov identifier NCT04120493) [23][24][25]. Although viral delivery systems are unquestionably powerful tools to further cellular uptake and expression of miRNAs, various complications such as immunogenicity have been reported [63]. The outcome of clinical trials such as the one for amiRNA drug AMT-130 must be awaited before a further judgment can be drawn.…”
Section: Open Accessmentioning
confidence: 99%
“…Several therapeutic interventions are being employed to overcome rAAV immunogenicity to improve the predictability and longevity of gene therapy. 38,39 The choice of therapeutic agents originates from Corticosteroids in the form of prednisone and prednisolone are the most commonly employed immune-modulatory agents. They demonstrate both anti-inflammatory and immunosuppressive properties with broad inhibitory effects on innate and adaptive cells by reducing the production of proinflammatory cytokines, chemokines, and T cells.…”
Section: Immunosuppressants Used In Gene Therapy Clinical Trialsmentioning
confidence: 99%
“…Several therapeutic interventions are being employed to overcome rAAV immunogenicity to improve the predictability and longevity of gene therapy 38,39 . The choice of therapeutic agents originates from their use in other autoimmune disorders or organ transplantation and trial and error.…”
Section: Gene Therapy and Management Of Immunosuppressionmentioning
confidence: 99%